Export-Platform FDI - Antràs, Pol,Fadeev, Evgenii,Fort, Teresa C.,Tintelnot, Felix (National Bureau of Economic Research, 2024)
We develop a model of export-platform foreign direct investment (FDI) in which final goods are produced only with labor and there are no fixed costs of exporting. We derive a simple condition that determines whether an MNE's plants are substitutes or complements. This condition is shaped by the relative size of (i) the cross-firm elasticity of demand the MNE faces for its goods and (ii) the within-firm elasticity of labor substitution across the MNE's plants. In two extensions of the model, we show that this complementarity is enhanced by firm-level (rather than plant-level) fixed costs of exporting and of sourcing inputs
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Multinationales Unternehmen; Auslandsinvestition; Theorie; Trade; International Factor Movements and International Business; Macroeconomic Aspects of International Trade and Finance